Antenatal care awareness among rural pregnant women of Uttar Pradesh, India: a community-based study - Jaiswal, Sudha; Shankar, Ravi; Jaiswal, Sandeep K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: A great deal of research evidence indicates that inappropriate antenatal care (ANC) increases the likelihood of maternal morbidity and maternal mortality. The adverse effects can be minimized if pregnant women are aware to ensure necessary registration, regular antenatal check-ups, and early diagnosis of high-risk pregnancy. The present study was conducted to explore the ANC awareness of pregnant women and its association with socio-demographic factors. Methods: A cross-sectional community-based study was conducted on 605 pregnant women who registered were at the primary health center (PHC) of Harhua block of Varanasi district, Uttar Pradesh. The self-developed ANC awareness schedule (ACAS) was used to assess the ANC awareness of pregnant women. Statistical analysis was performed using statistical package for the social sciences (SPSS) version 20 software. Results: Among 605 study participants, the majority of them (62.48%) were in the age group of 20–25 years. Out of 10.74% of study participants were illiterate while only 21.65% were graduated. Most of the pregnant women were from the lower middle class (44.30%), and only 3.47% belonged to the upper class. The study reveals that 57.36% of pregnant women were found to be aware of ANC. Out of 86.61% of pregnant women knew that regular antenatal check-up was necessary once they became pregnant. Socio-demographic variables such as category, education, occupation, and socioeconomic status of pregnant women were found to be significantly associated with ANC awareness. Conclusions: The level of awareness regarding ANC among pregnant women was not found satisfactory. They do not have proper knowledge and awareness about the various parameters of ANC. Improving awareness of ANC among pregnant women will enable them to detect high-risk pregnancies at the right time, which will also increase their chances of a healthy delivery.